Current problems and suggestions for the marketing and use of medical products in the field of animal health and breeding - Burak Mat; Mustafa Bahadır Çevrimli; Aytekin Günlü (Eurasian Journal of Veterinary Sciences)
Aim: In this study, the current situation in the supply, use and marketing of medicinal products of the veterinary clinic, policlinic and animal hospital services in Konya, Aydın, İstanbul and İzmir provinces has been tried to be revealed. Materials and Methods: The data of the study were obtained from the enterprises with data collection form, operating in 4 different cities (56 of them total).Simple random and snowball sampling methods were used in the determination of the enterprises included in the study.A 5-point Likert-type scale was applied for the opinions of the responsible veterinarian. Results: Within the scope of the survey, 30,4% of the organizations interviewed are in İzmir, 33,8% in Konya, 17,9% in Istanbul and 17,9% in Aydın. In the proportional distribution of business revenues, the gains obtained from patient visit fees were ranked first with 24%, artificial insemination revenues are second with 19% and the income from chemical agents such as drugs was the third with 16%. It has been reported that the primary factor in the supply of medicines is the drug's effectiveness and the most important problem in marketing is the difficulty of collecting money from customers. It has been reported that the most important factor in spot market formation is the veterinarians themselves. Conclusion: Distribution of medicines for solving the problems encountered, sales process, monitoring after the licensing process, etc. it is necessary to establish a comprehensive legislation covering all aspects. The findings of the study reveal that the e-prescription system, which has recently been introduced into practice, is an important opportunity in terms of eliminating existing problems completely and making the industry closed to unjustified and unfounded accusations. It has been agreed that an e-prescription system should be planned to encourage animal owners / breeders and veterinarians to achieve the desired goal.